IMPLIKASI REVIVALISME ISLAM DI INDONESIA - Rasfiudin; Rionaldi (JURNAL CERDAS HUKUM, 2022)
Islamic revivalism is a contemporary idea and thought that seeks to restore the glory of Islam. This movement emerged against the background of the decline that occurred in the Islamic world in almost all lines. In addition, the internal and external problems of the Islamic ummah are also a fundamental reason why this revivalism is present and has become a fairly intense discussion in the midst of the world community and especially the Muslim community. This revivalism appears in various Islamic countries, so that the forms of revivalism movements that occur in each country have their own differences and characteristics. Likewise in Indonesia, the revivalism movement in Indonesia began to emerge and develop along with the times and social demands. The revivalism movement in Indonesia is in the form of a political party platform and some uses a social organization platform. For this reason, this paper will try to look at the opportunities and challenges for the development of the revivalism movement in Indonesia. And what are the implications of the revivalism movements in Indonesia